2022
DOI: 10.3390/electronics11142265
|View full text |Cite
|
Sign up to set email alerts
|

EEG-Based Schizophrenia Diagnosis through Time Series Image Conversion and Deep Learning

Abstract: Schizophrenia, a mental disorder experienced by more than 20 million people worldwide, is emerging as a serious issue in society. Currently, the diagnosis of schizophrenia is based only on mental disorder diagnosis and/or diagnosis by a psychiatrist or mental health professional using DSM-5, a diagnostic and statistical manual of mental disorders. Furthermore, patients in countries with insufficient access to healthcare are difficult to diagnose for schizophrenia and early diagnosis is even more problematic. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 26 publications
0
5
0
3
Order By: Relevance
“…In recent years, many research studies have been performed to acquire informative features from EEG signals for the detection of schizophrenia [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. These studies reported various algorithms based on various features to characterize the.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, many research studies have been performed to acquire informative features from EEG signals for the detection of schizophrenia [15,16,17,18,19,20,21,22,23,24,25,26,27,28]. These studies reported various algorithms based on various features to characterize the.…”
Section: Introductionmentioning
confidence: 99%
“…In literature, very few research works have been performed on deep learning (DL) for detection of schizophrenia in EEG (e.g. we found few works [ 24 , 26 , 28 ]) but the methods are still limited in their ability to balance the efficiency and accuracy of schizophrenia detection. In addition, we also explored some recent works of schizophrenia detection that used Magnetic resonance images (MRI) data [ 29 , 30 , 31 , 32 , 33 , 34 ] as reported in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…EEG signals have been utilized in the diagnosis of various neurological disorders by extracting distinctive features and employing different classifiers in automated detection systems. EEG signals have been employed for the automatic detection of neurophysiological conditions such as alcoholism [7], dementia [8], epilepsy [9], schizophrenia [10], Parkinson's disease [11], and depressive disorders [12]. The EEG patterns of children with ADHD display differences in complexity, randomness, amplitude, and frequency compared with those of typically developing children.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, research plays a vital role in challenging misconceptions, reducing stigma, and promoting a more inclusive and supportive environment for individuals living with schizophrenia. Electroencephalography (EEG), while not a standalone diagnostic tool for schizophrenia, offers valuable insights into the disorder's neural dynamics and functional abnormalities due to its high temporal resolution [6][7][8].…”
Section: Introductionmentioning
confidence: 99%